Representasi Feminisme Dan Kesamaan Hak Bagi Disabilitas: (Studi Analisis Semiotika Charles Sanders Peirce Pada Iklan “Wardah Beauty Move You”) - Putri Ullya; Rizka Henny Maya Meutia (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
The lifestyle of modern society is not free of the name mass media as its properties grow and become its own phenomenon in the communication process, one of the most widely used mass media nowadays is television. In semiotics studies it views social phenomena in society and culture as signs, semiotics study systems, rules, and conventions that enable such signs to have meaning. As a method of analysis, there are some approaches that can be used for semiotics analysis. To examine the advertisements for human cosmetics in the study, the data analysis used is a semiotics analysis of Charles sanders peirce with the sense triangle theory that it claims. Peirce sees the sign (representation) as part of the object's reference is seita the subject's understanding of the sign. The study is used to learn about beauty analysis in more in-depth cosmetic ads. The data used in this study is not statistical data but descriptive, in words, not Numbers.